Neoadjuvant Docetaxel Plus Carboplatin Versus Epirubicin Plus Cyclophosphamide Followed by Docetaxel in Triple-Negative, Early-Stage Breast Cancer - Rana Atique Anwer, Sajid Ghafor, Huma Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the safety and efficacy of epirubicin and cyclophosphamide followed by docetaxel versus docetaxel and carboplatin chemotherapy in triple-negative, early-stage breast cancer (TNBC). Methodology: A prospective study was conducted in the oncology ward of Nishtar Hospital, Multan, from 3rd Mar 2021 to 3rd Mar 2022. A total of 70 TNBC women were included in the study and were divided into two groups. Group DC (35 patients) was administered docetaxel plus carboplatin and then underwent a mastectomy. Group ECD (35 patients) was administered epirubicin plus cyclophosphamide followed by docetaxel underwent mastectomy. Both groups received radiotherapy after mastectomy. Results: In group A, 21 patients (60.0%) achieved a pCR (95% CI 46.0-74.3), 13 patients (38.1%) achieved a pCR (95% CI 23.1-52.0). The difference between both groups was 21.9% (OR 2.49, 95% CI 2.2-42.5; p=0.002); hence non-inferiority was met. DCb regimen showed improved results compared to the EC-D regimen (p=0.039). After 1-year follow-up, it was observed that overall survival and event-free rates did not differ significantly between both groups. Conclusion: Docetaxel along with carboplatin demonstrated higher pCR than that of anthracycline and taxane-based treatment regimens. However, no significant difference was found between the two in terms of overall survival and event-free survival. Surprisingly, docetaxel and carboplatin caused a higher incidence of treatment-associated adverse effects. Keywords: Chemotherapy, radiotherapy, mastectomy, triple-negative breast carcinoma.